Reliability of “MB-Ruler Software” to Measure Craniovertebral Angle Using the Photographic Method - Kadu, Dipti Vilas; Shetye, Jaimala Vijay (Journal of Health and Allied Sciences NU, 2022)
Background The craniovertebral angle (CV angle) measurement is a convenient and easy clinical method for the cervical posture assessment. “Markus Bader (MB) ruler software” assists to measure angles and distances on the computer screen. The MB-ruler protractor is almost transparent; hence, it can be easily used on the computer screen. Many studies in physiotherapy have used this software for postural assessment with the photographic method, but the reliability of this software is not available to our knowledge in the Indian population.Aim The aim of this study was to find inter-rater and intra-rater reliabilities of “MB-Ruler software”, by using the photographic method to measure the CV angle for the cervical postural assessment.Study Design This is an observational study in healthy young population.Subjects and Method Total 30 young student volunteers with no clinical symptoms were enrolled for this study. A single standard lateral view image in a sitting position was used for CV angle measurement with “MB ruler software.” Three readings of the CV angle were taken by three different observers (A, B, and C) separately at intervals of time. The CV angle measured by three observers was compared.Results Cronbach's ɑ coefficient value for intra-rater (ICC 0.999) (intra-class correlation coefficient) as well as inter-rater (ICC 0.892) reliability for measuring CV angle was very high.Conclusion MB ruler demonstrates high intra-rater and inter-rater reliabilities and can be used for the photographic evaluation of posture by assessing the CV angle.
Keywords: MB ruler software; intra-rater reliability; inter-rater reliability; photographic postural assessment